2009
DOI: 10.1097/ico.0b013e3181839aee
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Herpes Simplex Virus Keratitis

Abstract: Children with HSV keratitis are at risk for recurrent keratitis and amblyopia. Prolonged systemic antiviral prophylaxis may help to prevent such consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 23 publications
(27 reference statements)
3
27
0
1
Order By: Relevance
“…Several studies have also reported that IRF-3 has anti-inflammatory properties which may help control immune-mediated pathology (Hua et al, 2002; Suh et al, 2009; Tarassishin et al, 2011a, 2011b). These studies therefore prompted us to investigate in this study whether a dysfunctional immune response was contributing to the observed pathology and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also reported that IRF-3 has anti-inflammatory properties which may help control immune-mediated pathology (Hua et al, 2002; Suh et al, 2009; Tarassishin et al, 2011a, 2011b). These studies therefore prompted us to investigate in this study whether a dysfunctional immune response was contributing to the observed pathology and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…There is a high risk of visual impairment and recurrences, and prolonged systemic treatment may be required. 2 Limbal stem cell deficiency can be primary, as in aniridia, or secondary, such as in chemical injuries or StevensJohnson syndrome. The hallmark is conjunctivalization of the corneal surface, and it may lead to PEDs and scarring.…”
Section: Causesmentioning
confidence: 99%
“…Early recognition and treatment of this group of diseases are critical because the visual consequences of corneal scarring in a child in the amblyogenic age group can be devastating. 1,2 Allergic Eye Diseases Ocular allergy affects up to 40% of the population, including both adults 3 and children, 4 and encompasses a spectrum of disorders. Six main clinical forms have been described: acute allergic conjunctivitis (AAC) seasonal allergic conjunctivitis (SAC) perennial allergic conjunctivitis (PAC) vernal keratoconjunctivitis (VKC) atopic keratoconjunctivitis (AKC) giant papillary conjunctivitis (GPC)…”
Section: Introductionmentioning
confidence: 99%
“…Oral valacyclovir or famciclovir are acceptable alternatives in older children 121. The pediatric use of topical trifluridine, vidarabine, and acyclovir ointment has also been described 121,123,124. There have been no reports to date on the use of topical ganciclovir specifically in children, although Phase II studies included children ≥2 years of age.…”
Section: Pediatric Usementioning
confidence: 99%